Investigation on the Flow Structure and the Performance of an Annular Diffuser with Two Different Types of Struts (Journal of Informatics and Mathematical Sciences, 2018)
In this present work, the flow structure and the performance of an annular diffuser are discussed. Two types of struts were used namely baseline struts and tapered struts. A Five-hole pitot pressure probe with a digital manometer was used to measure pressure. A DANTEC Dynamics make constant temperature anemometer with X-probe was used to measure mean velocity, turbulence level in axial and tangential directions. The numerical investigation was carried out by using STAR-CCM+, a commercial Computational Fluid Dynamics code. The experimental results are compared with CFD results. The results suggested that tapered design performed well compare with the baseline design.
Keywords: Annular diffuser; Hotwire anemometer; Pressure recovery; Strut; CFD